Seismic performance of mid-rise reinforced concrete buildings in Izmir Bayrakli after the 2020 Samos earthquake. (July 2022) - Demirel, Ismail Ozan; Yakut, Ahmet; Binici, Baris
Graphical abstract: Highlights: Damage survey conducted on poorly performed 140 reinforced concrete buildings. The deficiencies in buildings leading to extensive damage were identified. Most of the collapsed buildings suffered ground floor failures due to soft story. The decisive role of infill walls on the seismic performance of the RC buildings was observed. Local soil conditions and basin effects amplified the ground motion leading to localized damage. Abstract: On October 30th 2020, offshores of Samos Island, Greece was hit by a shallow earthquake of Mw  = 6.9 moment magnitude. Located 76 km away from the earthquake's epicenter, the mid-rise reinforced concrete (RC) building stock of the densely populated Izmir Bayrakli district experienced the most severe structural damage. Although the horizontal peak ground acceleration recorded at the site (PGA = 0.11 g) was well below design values recommended by the past and the present Turkish seismic codes, many buildings suffered heavy damage and 12 buildings collapsed, resulting in a death toll of 117. This paper aims to identify the seismic performance of mid-rise infilled RC frame buildings in Bayrakli by investigating the ground motion recordings, local soil conditions, characteristics of the building stock and the observed damages. The structural performance of 140 RC buildings between 7 and 12 stories that have exhibited poor performance during the earthquake was inspected in detail based on the field surveys conducted right after the earthquake. A database was created documenting the number of stories, major seismic deficiencies, date of construction, geographic coordinates, damage state of structural members and masonry infill walls of the inspected buildings. The localization of structural damage could be partially attributed to the amplified long-distance seismic waves for 0.5–1.5 s periods range due to local soil conditions and basin effects. Seismic vulnerabilities, structural deficiencies and construction quality of the buildings played a significant role in the experienced damage intensity. The influence of infill walls on the seismic performance of RC frame buildings is also clearly observed for code-compliant as well as aseismic buildings.